Outage Probability of SSC Receivers in Correlated Rayleigh Fading Channel with Multiple Cochannel Interferers - Petrovic, I.; Stefanovic, M.; Anastasov, J.; Panic, S.; Djordjevic, G.; Milic, D. (Elektronika ir Elektrotechnika, 2010)
In this paper switch-and stay combining (SSC) receivers over the Rayleigh fading channels are observed. The case of interference-limited system in the environment with multiple cochannel interferers is considered. Proposed analysis gives new formula for evaluating the outage probability. Based on analytical results some numerical are obtained pointing out the influence of interferers and level of correlation to the outage probability. Monte Carlo simulations are also presented in order to confirm the validity and accuracy of the derived analytical expressions.